Therapeutic Drug Monitoring in Italian Psychiatry - Conca, A.; Schmidt, E.; Pastore, M.; Hiemke, C.; Duffy, D.; Giupponi, G. (Pharmacopsychiatry, 2011)
Therapeutic drug monitoring (TDM) aims to optimize pharmacotherapy treatment. Knowledge, availability and use of TDM for psychiatric patients, however, differ between countries. In this survey we analysed the practice in Italy of TDM for psychoactive drugs.A semi-structured questionnaire was sent out to 211 mental health centres (centro di salute mentale) and 10 university hospitals from each region in Italy.Feedback was obtained from 44 centres. Information collected by the questionnaires indicated that in Italian psychiatry TDM is used for lithium, valproic acid and carbamazepine. With regard to clozapine, TDM was regarded as the blood cell counting which is obligatory when prescribing this drug. TDM was not employed for antidepressant or antipsychotic drug prescribing. Moreover, it appeared that only a few laboratories in Italy offer TDM services for psychiatric patients. Nevertheless, interest was expressed about receiving further information about TDM in psychiatry and participating in training programmes.This nationwide survey revealed that in Italy, TDM of psychoactive drugs is restricted to only a few drugs. In response to interest expressed, mental health workers should be educated about TDM and more laboratories should be encouraged to establish TDM services for psychotropic drugs.
Keywords: therapeutic drug monitoring; psychoactive drugs; plasma concentration; Italy; TDM service